2012
DOI: 10.1002/sca.21030
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Epoxy‐Based Sealer Residues in Dentin Treated With Different Chemical Removal Protocols

Abstract: The presence of residual endodontic sealer in the pulp chamber may cause discoloration of the dental crown and interfere with the adhesion of restorative materials. The aim of this study was to compare the efficacy of different solvents in removing residues of an epoxy resin-based sealer (AH Plus) from the dentin walls of the pulp chamber, by scanning electron microscopy (SEM). Forty-four bovine incisor dental crown fragments were treated with 17% EDTA and 2.5% NaOCl. Specimens received a coating of AH Plus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(96 citation statements)
references
References 20 publications
0
92
0
4
Order By: Relevance
“…19,21 The concept that "like dissolves like" (polar solvents are better at dissolving polar substances), and vice versa explains the higher incidence of remaining sealer residues for the cleaning protocol employing ethanol. 9 Kuga et al 7 have observed, through SEM, that the 95% ethanol and isopropyl alcohol are ineffective in cleaning dentin impregnated with AH Plus sealer. In the present study, the surface.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…19,21 The concept that "like dissolves like" (polar solvents are better at dissolving polar substances), and vice versa explains the higher incidence of remaining sealer residues for the cleaning protocol employing ethanol. 9 Kuga et al 7 have observed, through SEM, that the 95% ethanol and isopropyl alcohol are ineffective in cleaning dentin impregnated with AH Plus sealer. In the present study, the surface.…”
Section: Resultsmentioning
confidence: 99%
“…7,20,21 Ethanol is routinely recommended as a chemical solution for removal of sealers from the pulp chamber; however, ethanol cannot completely remove the sealer residues from dentin. 7 Although xylol is recommended as a solvent for epoxy resin-based sealer, it also does not completely remove sealer residues from the dentin surface.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations